Antiviral activity of an ACE2-Fc fusion protein against SARS-CoV-2 and its variants. - Ernesto Bermúdez-Abreut; Talia Fundora-Barrios; Diana Rosa Hernández Fernández; Enrique Noa Romero; Anitza Fraga-Quintero; Ana V Casadesús Pazos; Briandy Fernández-Marrero; Claudia A Plasencia Iglesias; Marilyn Clavel Pérez; Katya Sosa Aguiar; Belinda Sánchez-Ramírez; Tays Hernández (PLoS ONE)
SARS-CoV-2 has continued spreading around the world in recent years since the initial outbreak in 2019, frequently developing into new variants with greater human infectious capacity. SARS-CoV-2 and its mutants use the angiotensin-converting enzyme 2 (ACE2) as a cellular entry receptor, which has triggered several therapeutic strategies against COVID-19 relying on the use of ACE2 recombinant proteins as decoy receptors. In this work, we propose an ACE2 silent Fc fusion protein (ACE2-hFcLALA) as a candidate therapy against COVID-19. This fusion protein was able to block the binding of SARS-CoV-2 RBD to ACE2 receptor as measured by ELISA and flow cytometry inhibition assays. Moreover, we used classical neutralization assays and a progeny neutralization assay to show that the ACE2-hFcLALA fusion protein is capable of neutralizing the authentic virus. Additionally, we found that this fusion protein was more effective in preventing in vitro infection with different variants of interest (alpha, beta, delta, and omicron) compared to the D614G strain. Our results suggest the potential of this molecule to be used in both therapeutic and preventive settings against current and emerging mutants that use ACE2 as a gateway to human cells.